Principles of Cooperation in Assertive and Commissive Speech Acts in Dialogue among Film Characters Teach Me Islam Director Deni Pusung - Tia Fijri Astuti; Herwandi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This research is entitled the principle of assertive and commissive cooperation in dialogue between figures Film “ajari aku islam”. phenomena that are found in everyday language carried out by humans, very much use assertive and commissive speech. Besides being widely used by humans, assertive and commissive speech is also widely used in human creations, namely cinematography (films), novels and other copyrighted works that use language. The research problem is how is the maxim of the principle of cooperation in each form of assertive and commissive speech in the dialogue between the characters of the film Ajari Aku Islam directed by Deni Pusung. This study aims to describe, analyze, interpret, and conclude the maxims of the cooperative principle in each form of assertive and commissive speech. In this study, the researcher refers to the theory proposed by Rahardi Kunjana. This research method is a qualitative method. The technique used in this research is the agih technique. The results of the study show that the Assertive Speech Act of Dialogue Between Film Characters Ajari Aku Islam Director Deni Pusung consists of 29 utterances, commissive speech act dialogue between Ajari Aku Islam film characters Director Deni Pusung consists of 10 utterances, the maxim of quantity in the form of assertive and commissive speech consists of 9 data, maxim of quality in assertive and commissive form consists of 10 data, maxim of relevance in assertive and commissive form consists of 4 data.